2017
DOI: 10.1016/j.anucene.2016.11.035
|View full text |Cite
|
Sign up to set email alerts
|

A new Monte Carlo method for neutron noise calculations in the frequency domain

Abstract: A new Monte Carlo algorithm that solves the transport equations for the neutron noise in the frequency domain has been developed. Neutron noise equations, which are obtained by assuming small perturbations of macroscopic cross-sections around a steady state in the neutron field and by subsequently taking the Fourier transform in the frequency domain, are usually solved by analytical techniques or by resorting to diffusion theory. A stochastic approach has been recently proposed in the literature by using parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…With respect to the noise measurement technique, a detailed characterization of the field of view of the detectors is required. A potential characterization for such field of view could be done through analog Monte Carlo calculations [9] where the response function of the detector to various patterns of local void content are calculated.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the noise measurement technique, a detailed characterization of the field of view of the detectors is required. A potential characterization for such field of view could be done through analog Monte Carlo calculations [9] where the response function of the detector to various patterns of local void content are calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that weight cancellation can be very effective in dealing with Monte Carlo problems using particles of both positive and negative weights [6,8,11,26]. In view of these considerations, in the following we will formally address the effect of cancellation on Eq.…”
Section: B Modeling Weight Cancellationmentioning
confidence: 99%
“…In the heterogeneous B 1 method, the angular neutron flux is factorized as where = the position vector, = the particle direction, E = the neutron energy, , and = the spatial fine structure of the neutron flux within a unit cell. Rouchon et al (2017). This paper adopts another way as follows.…”
Section: Critical Buckling Search and Directional Diffusion Coefficiementioning
confidence: 99%